### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The roots of x^2 - 5x + 6 = 0 are x = 2 and x = 3.

To find the roots of a quadratic equation in the form ax^2 + bx + c = 0, we can use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / 2a

In this case, a = 1, b = -5, and c = 6. Substituting these values into the quadratic formula, we get:

x = (-(-5) ± √((-5)^2 - 4(1)(6))) / 2(1)

x = (5 ± √(25 - 24)) / 2

x = (5 ± 1) / 2

So the roots of the equation are x = 2 and x = 3. We can check this by substituting these values back into the original equation:

2^2 - 5(2) + 6 = 0

3^2 - 5(3) + 6 = 0

Both of these equations are true, so we have found the correct roots.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...